Implementation of Financial Technology to Increase Interest of Saving the Millennial Generation of Sharia - Peni Haryanti; Athi’ Hidayati; Iesyah Rodliyah (Indonesian Economic Review, 2023)
This study aims to determine of how the implementation of Islamic finance increases the interest in saving the sharia millennial generation at the Hasyim Asy’ari Tebuireng University, Jombang in Indonesia. Financial technology is the latest breakthrough in modern Islamic financial technology that provides convenience for the public in terms of financial transactions. The method adopted in this research is descriptive quantitative method using data in the form of numbers which are then described. The results in this study indicate that the significant influence of the financial technology variable on the interest in saving Islamic millennial genesis. From the statements filled in by respondents, it shows that many respondents choose to agree (4) and strongly agree (5) from the statements which meaning that financial technology can increase the interest in saving the sharia millennial generation.